PENGEMBANGAN E-MODUL AJAR BERBASIS FLIPBOOK PADA MATA KULIAH PROGRAM PENGEMBANGAN KELOMPOK BERMAIN ANAK USIA DINI: PENGEMBANGAN E-MODUL AJAR BERBASIS FLIPBOOK PADA MATA KULIAH PROGRAM PENGEMBANGAN KELOMPOK BERMAIN ANAK USIA DINI - Ningsih, Sulastya; Nuraini, Febritesna; Hardiyanti, Waode Eti; Setiyowati, Endah (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2024)
Increasing student knowledge requires the availability of adequate learning resources to support the learning process. The development of kvisoft flipbook-based teaching materials is one of the important components to attract students' attention, is easy to understand and can be accessed anywhere so that students can study independently and get good quality learning outcomes. The purpose of this research is to determine the design process for developing flipbook-based e-modules, the feasibility of e-modules, and determine student responses to e-modules teaching. This research method is the development of Research and Development using the ADDIE model which in its implementation uses 5 stages, namely: analysis, design, development, implementation, and evaluation. Limited trial with 50 third-semester students of PGPAUD UNG. Based on the results of the material validation assessment, media experts got score of 98.89% in the "very strong" interpretation category and student response sheets score of 89.45% in the "very strong" interpretation category. Therefore, that students have the motivation to learn independently, are able to review learning so that in class learning becomes two-way and student-centered. However, in this research, the researcher only applied basic competencies for compiling material in e-modules with the help of kvisoft flipbook so that in future research they can develop e-modules in other basic competencies and use a high-level approach that can help hone students' abilities in other subjects so that they can improve their skills in other subjects. there have been many developments in teaching materials that are easy for students to use in independent study.